Influence of Fertilizers with Prolongation Effect on Productivity of Root-Crop Vegetables and Biochemical Composition Before and After Storage - Bundinienė, Ona; Kavaliauskaitė, Danguolė; Starkutė, Roma; Jankauskienė, Julė; Zalatorius, Vytautas; Bobinas, Česlovas (IntechOpen, 2012)
None